2008
DOI: 10.1175/2007jamc1714.1
|View full text |Cite
|
Sign up to set email alerts
|

Polarimetric Radar Observations at Low Levels during Tornado Life Cycles in a Small Sample of Classic Southern Plains Supercells*

Abstract: Preliminary schematics of polarimetric signatures at low levels in southern plains classic supercells are developed for pretornado, tornado, and tornado demise times from a small collection of cases, most of which are cyclic tornado producers. Characteristic signatures and patterns are identified for the reflectivity factor (Z HH ), the differential reflectivity (Z DR ), the correlation coefficient ( hv ), and the specific differential phase (K DP ). Signatures likely related to an ongoing tornado are also dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 22 publications
4
21
0
Order By: Relevance
“…Van Den Broeke et al (2008) report qualitatively that hail shafts as inferred from high Z HH and low Z DR are present most often at times leading up to tornadogenesis in the few cases they investigated. It is clear from the present analysis that the relationship between the hail signature appearance and tornado presence is weak and highly dependent on the individual storm characteristics, which can differ substantially in different climate regions; for example, Oklahoma (Great Plains) supercells produce very large hail more often than Alabama (Gulf Coast) storms (Doswell et al 2005).…”
Section: B Hail Signature In the Forward-flank Downdraftmentioning
confidence: 62%
See 1 more Smart Citation
“…Van Den Broeke et al (2008) report qualitatively that hail shafts as inferred from high Z HH and low Z DR are present most often at times leading up to tornadogenesis in the few cases they investigated. It is clear from the present analysis that the relationship between the hail signature appearance and tornado presence is weak and highly dependent on the individual storm characteristics, which can differ substantially in different climate regions; for example, Oklahoma (Great Plains) supercells produce very large hail more often than Alabama (Gulf Coast) storms (Doswell et al 2005).…”
Section: B Hail Signature In the Forward-flank Downdraftmentioning
confidence: 62%
“…Recent work by Van Den Broeke et al (2008) analyzes multiple supercell cases. They present a preliminary climatology of polarimetric characteristics of southern Great Plains classic supercells, describing the temporal evolution of the polarimetric variables for several tornadic storms.…”
Section: Introductionmentioning
confidence: 99%
“…The details on the dual-polarization variables were provided by Kumjian (2013a, b, and c). Studies on the polarimetric characteristics of supercells can be found in Dotzek et al (2001), Loney et al (2002), Kumjian and Ryzhkov (2008), Van Den Broeke et al (2008), Snyder et al (2010Snyder et al ( , 2013, Palmer et al (2011), among others.…”
Section: Koun Polarimetric Radarmentioning
confidence: 99%
“…With the growing number of polarimetric Doppler weather radars, many studies have provided detailed observations of wind, hydrometeor type and distribution, and radar reflectivity within supercell thunderstorms (e.g., Bringi et al 1991Bringi et al , 1996Smyth and Illingworth 1998;Kennedy and Rutledge 1995;Hubbert et al 1998;Wurman and Gill 2000;Burgess et al 2002;Ryzhkov et al 2005;Bluestein et al 2007;Kumjian andRyzhkov 2008, 2009;Romine et al 2008;Van Den Broeke et al 2008). While polarimetric radar observations can provide information related to the microphysical character of thunderstorms, the microphysics of the near-surface environment, believed to be most important for tornadogenesis, is usually below the radar horizon of even mobile polarimetric radar platforms.…”
Section: Introductionmentioning
confidence: 99%